Розрахунок параметрів мас автобусів на етапі ескізного проектування - Войтків, Станіслав (Видавництво Львівської політехніки, 2018)
The calculation method of bus mass parameters, first of all kerb weight, at the stage of development of sketch projects. The empirical formulas for calculation buses kerb weight on the basis of known kerb weight of buses-analogues of similar or close construction and equipment are given.
The calculation of bus mass parameters at the stage of executive design
Keywords: 629.341